The aggressive call of Dendropsophus cruzi (Pombal & Bastos, 1998) (Anura; Hylidae) in Central Brazil - Andreani, Tainã Lucas; Oliveira, Seixas Rezende; Guerra, Vinícius; Bastos, Rogério Pereira; de Morais, Alessandro Ribeiro (Zootaxa, 2018)
Dendropsophus cruzi (Pombal & Bastos, 1998) is a small hylid (male snout-to-vent length = 16.3–19.4 mm; female SVL = 21.3–25.0 mm) that is allocated in the D. microcephalus group (Faivovich et al. 2005). It is commonly found in Open and forested areas from Central Brazil to Provincia Velasco, Departamento de Santa Cruz, Bolivia (Frost 2017; Tessarolo et al. 2016). Pombal & Bastos (1998) described the advertisement call of D. cruzi as a single pulsed note. Posteriorly, studies uncovered relationships between dominant frequency variation in the advertisement calls of D. cruzi and variation in the SVL and mass of males (Bastos et al. 2003), as well as the existence of a clinal geographic pattern in the variation of acoustic parameters of these calls (Tessarolo et al. 2016). However, the acoustic communication in anurans is usually mediated by more than one vocalization type (Toledo et al. 2015). Due the importance of call types in the social context of anurans (e.g., Reichert 2011; Forti et al. 2017), we expand the vocal repertoire of D. cruzi by describing its aggressive call.